No worry, dat sick go finish small time : Encouraging local community participation in global healthcare via minority language de-terminologization and ruralization. - Tekwa, Kizito; Tazoacha, Francis (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
This study evaluates the dual role of translators and interpreters working for NGOs involved in the health sector in developing countries. Given the crucial importance of public health in a nation’s development, we assess the way grassroots participation in healthcare projects and activities is enhanced through the translation of healthcare information into low-resource languages. This study, epistemologically grounded in the theory of planned behaviour (TPB), adopts a qualitative and quantitative methodological approach to correlate the TPB and the target-language choices of translator-interpreters and the translation strategies they adopt working with low-resource languages. The survey responses and audio recordings analysed are those of translators or interpreters working in a rural context in the Anglophone regions of Cameroon. The target language in question is Pidgin English, a low-resource oral language. The evidence gathered leads to the finding that various de-terminologization strategies are employed to ensure that messages are adequately disseminated and that the local community members are involved in healthcare activities. The study seeks to bring together translation, interpreting, the TPB, and international development in which the involvement of NGOs underscores North–South cooperation in the strategic domain of global healthcare.